Treatment of pathological gambling and relapse prevention - Banaco, Roberto Alves (Brazilian Journal of Behavioral and Cognitive Therapy, 1999)
Gambling behavior has been classified as pathological under certain conditions and has been compared to impulse dysfunction. This way, the use of procedures similar to that applied to those dysfunction has been proposed as therapeutic treatment. A proposal of possible functional relationships involved in the problem is presented: classic conditioning; intermittence of positive reinforcement; avoidance responses of uncomfortable internal states; money while generalized reinforcer can have accessory role. Are still analyzed some therapeutic proposals: involving the family in the therapeutic process; applying the procedure of successive approaches for obtaining of the control on playing and techniques of relapse prevention.